The Analysis of Electrode Combination Effect on Steel and Stainless Steel Welding (Overview of Tensile and Metallography Test) - Ikhwani, Hasan; Abdullah, Faruq; Pratikno, Herman; Sujantoko, Sujantoko; Hadiwidodo, Yoyok Setyo; Yulianto, Totok (Institut Teknologi Sepuluh Nopember, 2024)
The process of building a ship or offshore structure, proper and accurate planning and implementation is required. In the development process, it will go through a stage, namely the construction stage. At the construction stage, the construction of a ship or offshore building will go through a welding phase which functions as a connection of materials to one another. Low carbon steel and stainless steel are materials that are often used in the construction process of ships or offshore structures. In this study, an analysis of the effect of the combination of electrodes on the welding of steel and stainless steel materials was carried out in terms of mechanical properties such as tensile strength, bending strength and metallographic shape. The materials used in this study were A36 steel and 304 stainless steel, while the electrode combinations used were E308L and E309 electrodes. Welding variations used in this study were a combination of E308L (root) and E309 (filler) electrodes, a combination of E308L (filler) and E309 (root) electrodes, E309 electrodes, and E308L electrodes. In the tensile test results it was found that the highest tensile strength value occurred in Specimen 4 with an average value of yield strength and ultimate strength of 389.54 MPa and 522.52 MPa. The tensile strength value is influenced by the amount of chromium contained in the electrode. This is because the higher the amount of chromium causes the amount of ferrite in the material to increase so that the tensile strength value decreases. In the metallographic macro testing results, the best weld profile results were obtained on specimens with the ME 4 material code because the results of the weld profile shape best met ASME Section IX standards. The results of micro metallographic testing showed that welding using the dominant E308L electrode as in Specimen 1 and Specimen 4 obtained a higher ultimate strength value compared to Specimen 2 and Specimen 3. This was due to the influence of chromium on the electrodes used, high chromium causing the formation of a ferrite phase in the microstructure of the material.